INCIDENCE OF RIGHT VENTRICULAR INFARCTION IN PATIENTS WITH INFERIOR WALL MYOCARDIAL INFRACTION - ALI , L; SHAHID , M; KHAN , MA; SHAHZAD , A; SALEEMI , MS; HASHMI , KA (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in the Department of Cardiology, Nishtar Medical Hospital & CPEIC Multan from August 2020 to February 2021 to evaluate the frequency of right ventricular infarction in subjects with inferior wall myocardial infarction. A total of 110 patients were included. Age, gender, smoking history, dyslipidemia, diabetes mellitus, and hypertension were recorded. Clinical and radiographic examination was done, and the right ventricular infarction was recorded accordingly. Results showed that of 110 subjects, 43 (39.09%) had right ventricular infarction. Thus, it was concluded that right ventricular infarction is highly prevalent in subjects with inferior wall myocardial infarction. Early diagnosis and treatment are important for reducing morbidity and mortality.